Expertise in evidence-based medicine: a tale of three models - Wieten, Sarah (Philos Ethics Humanit Med, 2018)
BACKGROUND: Expertise has been a contentious concept in Evidence-Based Medicine (EBM). Especially in the early days of the movement, expertise was taken to be exactly what EBM was rebelling against—the authoritarian pronouncements about “best” interventions dutifully learned in medical schools, sometimes with dire consequences. Since then, some proponents of EBM have tried various ways of reincorporating the idea of expertise into EBM, with mixed results. However, questions remain. Is expertise evidence? If not, what is it good for, if anything? METHODS: In this article, I describe and analyze the three historical models of expertise integration in EBM and discuss the difficulties in putting each into practice. I also examine accounts of expertise from disciplines outside of medicine, including philosophy, sociology, psychology, and science and technology studies to see if these accounts can strengthen and clarify what EBM has to say about expertise. RESULTS: Of the accounts of expertise discussed here, the Collins and Evans account can do most to clarify the concept of expertise in EBM. CONCLUSIONS: With some additional clarification from EBM proper, theoretical resources from other disciplines might augment the current EBM account of expertise.